2016
DOI: 10.4103/0976-9668.175106
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral conjunctivitis of unique etiology: A case report from Eastern India

Abstract: A middle-aged female patient from West Bengal presented with complaints of redness, foreign body sensation, and watering for 2 days in the left eye. Slit lamp examination of the left eye revealed several minute white foreign bodies moving over the bulbar conjunctiva. Removal of the foreign bodies under local anesthesia, followed by microscopic examination, suggested the presence of first instar larvae of Oestrus ovis; the sheep nasal bot fly. Diagnosis of unilateral external ophthalmomyiasis was made. Such cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Clinicians must consider ophthalmomyiasis a possibility in patients exhibiting nonspecific symptoms, as demonstrated in this study and various others [26]. Failure to do so in endemic areas or tourists returning from such regions may lead to mistaking ophthalmomyiasis for other forms of conjunctivitis [30]. Symptoms typically resemble acute catarrhal conjunctivitis and include burning, stinging, itching, increased tearing, and the sensation of a foreign object in the eye [10].…”
Section: Clinical Manifestationsmentioning
confidence: 86%
See 3 more Smart Citations
“…Clinicians must consider ophthalmomyiasis a possibility in patients exhibiting nonspecific symptoms, as demonstrated in this study and various others [26]. Failure to do so in endemic areas or tourists returning from such regions may lead to mistaking ophthalmomyiasis for other forms of conjunctivitis [30]. Symptoms typically resemble acute catarrhal conjunctivitis and include burning, stinging, itching, increased tearing, and the sensation of a foreign object in the eye [10].…”
Section: Clinical Manifestationsmentioning
confidence: 86%
“…India has experienced a substantial number of external ophthalmomyiasis cases over the last two decades, as evidenced by nine case series studies, with Misra [78], while in the other 22 reports, one or two cases were reported [2,13,20,29,30,[62][63][64][65][79][80][81][82][83][84][85][86][87]. The causative agents identified in India were O. ovis, Musca ssp., Musca domestica Linnaeus (Insecta: Diptera: Muscidae), and C. bezziana.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Larvy Oestrus ovis však nejsou schopny vylučovat proteolytické enzymy, proto jsou většinou omezeny na vnější povrch oka [4]. V literatuře jsou uváděny vzácné případy komplikací jako jsou: podspojivkové krvácení (Obrázek 2), vřed rohovky, zhoršený zrak, intraokulární invaze s endoftalmitidou, iridocyklitida a dokonce slepota [5].…”
unclassified